The Influence of English Proficiency on Vocational Students' Speed in Solving Network Troubleshooting Tasks: A Study at SMK Prawira, Carita, Pandeglang, Banten - N. Erna Marlia Susfenti; Naylur Rosyid (Beginner: Journal of Teaching and Education Management, 2025)
This study investigates how technical English proficiency influences the speed at which students in Computer and Network Engineering (TKJ) resolve network troubleshooting problems. Conducted at SMKS Prawira, Carita, Banten, this ex post facto study involved 42 students who completed a technical English test and performed simulated troubleshooting scenarios using Cisco Packet Tracer. The results show a strong negative correlation (r = -0.934) between English proficiency and troubleshooting time. Students with higher proficiency were able to resolve problems faster, highlighting the functional importance of technical English comprehension. The findings emphasize the necessity for vocational curricula to incorporate English for Specific Purposes (ESP), especially for technology-related fields. Integrating language and technical instruction could bridge the gap between communication skills and real-world problem-solving capabilities. This study advocates for targeted instructional modules and collaborative teaching approaches to enhance students’ readiness for industry demands.